PEMBERDAYAAN USAHA MIKRO KECIL DENGAN PENINGKATAN PRODUK PANGAN BERSERTIFIKAT HALAL MELALUI CORPORATE SOCIAL RESPONSIBILITY - Tarsisius Murwadji (Faculty of Law, Maranatha Christian University, 2020)
Halal food products are one part of Islamic Sharia, especially for Muslim consumers. The circulation of food products in Indonesia, one of which comes from the Micro Small Enterprises (MSEs), which also has an important role in improving the economy. Increasing the ownership of halal certificates for MSEs halal food products can be done through the Corporate Social Responsibility (CSR) program provided by the stakeholders. The research method used in this research is normative juridical by emphasizing on literature study and supported by field data. The results of this study indicate that one of the empowerment for the development of MSEs can be through an increase in halal-certified food products given the halal product consumer market in Indonesia is very large. Improvement of halal-certified food products at MSEs can be through CSR programs specifically aimed at empowering and developing MSEs. In addition, through CSR programs, companies and other stakeholders can become MSEs partners in marketing halal-certified food products.